An N-terminal SIAH-interacting motif regulates the stability of the ubiquitin specific protease (USP)-19 (2013)
The Ubiquitin Specific Protease-19 (USP19) regulates cell cycle progression and is involved in the cellular response to different types of stress, including the unfolded protein response (UPR), hypoxia and muscle atrophy. Using the unique N-terminal domain as bait in a yeast-two hybrid screen we have identified the ubiquitin ligases Seven In Absentia Homolog (SIAH)-1 and SIAH2 as binding partners of USP19. The interaction is mediated by a SIAH-consensus binding motif and promotes USP19 ubiquitylation and proteasome-dependent degradation. These findings identify USP19 as a common substrate of the SIAH ubiquitin ligases. © 2013 Elsevier Inc.